Majelis An-Nadzir Gowa: dari Lembaga Keagamaan Ekslusif hingga Madrasah 19992019 - Nuryadin, AM. Alfauzan; Najamuddin, Najamuddin; Ahmadin, Ahmadin (Universitas Syiah Kuala, 2025)
This study examines the development of the education system at Majelis An-Nadzir Gowa, influenced by the teachings of K.H. Syamsuri Abdul Majid. The early education at this community was informal, focusing on basic skills such as reading, writing, arithmetic, and in-depth religious education. The education system was designed to foster independence and life skills, with an emphasis on Quran memorization and practical skills, such as agriculture and livestock management. This research uses historical research methods, with data collected through interviews, observations, and literature studies, and analyzed descriptively. The results of the study show significant changes after 2006, especially in 2012 with the introduction of a more structured class system. In 2019, Majelis An-Nadzir Gowa received operational permits as a non-formal educational institution, allowing them to manage education according to their own beliefs. This study concludes that the adaptation of the education system and collaboration with the government are crucial for the sustainability and quality of education at Majelis An-Nadzir Gowa.